HUBUNGAN KONSUMSI ALKOHOL, KEBIASAAN MEROKOK, DAN TINGKAT STRES DENGAN KEJADIAN HIPERTENSI USIA PRODUKTIF (Studi Di Wilayah Kerja Puskesmas Ngemplak Simongan Semarang) - Elsa Panji Sukma; Sri Yuliawati; Retno Hestiningsih; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Hypertension will continue to increase with age. Hypertension in productive age can lead to reduced productivity and quality of life in later age. Ngemplak Simongan Health Center has increased the number of cases by 3,750 cases in 2017. The purpose of this study was to determine the relationship of alcohol consumption, smoking habits, and stress levels with the incidence of productive age hypertension in the working area of Ngemplak Simongan Health Center Semarang. This study was an observational analytic study using a cross sectional study design. The sample used was 92 samples taken by simple random sampling. Data analysis used the chi square test with a significant level of 95%. The results of univariate analysis showed that the majority of respondents were female 70.7%, did not consume alcohol 98.9%, did not smoke 79.3%, high stress level 38.0%. From the relationship test results it can be concluded that there is no relationship between alcohol consumption and smoking habits, while stress levels are associated with the incidence of hypertension at age productive.